KAJIAN NILAI TUKAR DAN DAYA SAING KOMODITAS NELAYAN BAGAN RAMBO DI DESA MUARA TINOBU KECAMATAN LASOLO KABUPATEN KONAWE UTARA - Hermawan Hermawan; Onu La Ola; Hasnia Arami (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
This study aims to determine the profit of boat lift nets fisherman, to determine the competitiveness level of the fishing production, and to determinate the exchange rate of boat lift nets fishing product in the local market.  This study was conducted in September to Oktober 2013 in the Muara Tinobu Village, North Konawe. The method this study was used survey method, and sampling method was purposive sampling, which the number of respondents of this study were 9 fisherman. Based on this research, it is known that the profits of fishermen boat lift nets on a small scale of Rp34.445.007, median scale was Rp44.252.056 and the higher by Rp98.982.998.  Based on the analysis of the competitiveness of the fishing production of boat lift nets in the Muara Tinobu Village have high competitiveness. The exchange rate of the fisherman product of boat lift nets  on a small and median scale is already able to subsistence needs, while the fishermen of boat lift nets  with a higher scale high being able to meet the needs of subsistence, it also has the potential to consume the needs of secondary or tertiary, or to investation.Keyword : Exchange Rate, Competitiveness, Fisherman, Boat Lift, Konawe Utara